NILAI ANAK PEREMPUAN PADA KELUARGA TIONGHOA (STUDI KASUS KELUARGA TIONGHOA YANG MENYERAHKAN ANAK PEREMPUAN PADA KELUARGA LAIN DI BAGANSIAPIAPI) - Yusni Wati; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In Bagansiapiapi based on the 2018 field data, there are 30 Tionghoa girls living with host families. The phenomenon of surrendering female children to other families continues to this day. The purpose of this study was to identify the reasons for giving up the child and how the child actually brought the child when he was born. This study used a qualitative method, with 8 subjects consisting of key informants as many as 5 parents of girls who had been given when and additional informants were 3 community leaders, selected by purposive sampling technique. Data analysis techniques used are in-depth interviews and documentation. The theory of Weber's social action is still relevant to be used in understanding this research. The results showed that there were four reasons parents gave their daughters to other families because of poverty, Shio brought by children did not match one of the family members, did not want to care for more girls, and wanted to reduce family burden. This surrender social action was done because the Chinese ethnic group saw the value of girls as low. Both from religious values, social cultural values, economic values, and psychological values. So that every family who will surrender the child for various reasons is justified from the culture.Keywords: Child value, Tionghoa